Fabrication of a Gelatin-Based Microdevice for Vascular Cell Culture - Satoko Sasaki; Tomoko Suzuki; Kyojiro Morikawa; Michiya Matsusaki; Kae Sato (Micromachines, 2022)
This study presents a novel technique for fabricating microfluidic devices with microbial transglutaminase-gelatin gels instead of polydimethylsiloxane (PDMS), in which flow culture simulates blood flow and a capillary network is incorporated for assays of vascular permeability or angiogenesis. We developed a gelatin-based device with a coverslip as the bottom, which allows the use of high-magnification lenses with short working distances, and we observed the differences in cell dynamics on gelatin, glass, and PDMS surfaces. The tubes of the gelatin microfluidic channel are designed to be difficult to pull out of the inlet hole, making sample introduction easy, and the gelatin channel can be manipulated from the cell introduction to the flow culture steps in a manner comparable to that of a typical PDMS channel. Human umbilical vein endothelial cells (HUVECs) and normal human dermal fibroblasts (NHDFs) were successfully co-cultured, resulting in structures that mimicked blood vessels with inner diameters ranging from 10 µm to 500 µm. Immunostaining and scanning electron microscopy results showed that the affinity of fibronectin for gelatin was stronger than that for glass or PDMS, making gelatin a suitable substrate for cell adhesion. The ability for microscopic observation at high magnification and the ease of sample introduction make this device easier to use than conventional gelatin microfluidics, and the above-mentioned small modifications in the device structure are important points that improve its convenience as a cell assay device.